(untitled) (Medico Legal Update, 2021)
The present study was carried out on a period between December 2019 to February 2020 on 50 healthy patients, their ages ranged from eighteen to fifty years. They were 26 males and 24 females. These healthy patients were attending Baghdad Educational Hospital, Al-Harriri Hospital, and Al-Diwaniyah General Hospital in order to perform various surgeries. And after all tests are done. Then they were admitted to the operating theater. In this study used the general anesthesia method. And they were given drugs of anesthesia, during each step; the values of blood sugar levels (Mg) were measured. Such as pre induction, post induction, after incision, after fluid, and recovery. To know the effect of general anesthesia method on blood sugar levels in different times of operation on gender and age groups. This study showed that total numbers of patients were 50 including males about 26 (52.0%) and females about 24(48.0%), their age of all individuals ranged from less than 20 years old (<20-29) which number and percentage 22,44.0% to 50 years old 7 (14.0%). Also there are no significant difference was observed in the blood sugar levels changes (Mg) in both males and females (gender) before and after the operation or surgery, also no found any differences between blood sugar levels changes (Mg) at the age groups and the general anesthesia method, after and before the operation in different times of surgery. So in this study summarized the mean and stander deviation values according to the levels of blood sugar (Mg) among different times of surgery, and then show the mean of pre induction period about 83.84, While mean of values of blood sugar at post induction time at general anesthesia method about 104.94. Aims and Objectives: This study was investigated the influence of general anesthetic drugs that effect on the blood sugar level changes of patients with surgery. This was done with the following objectives: • To administer general anesthesia by using a different combination of drugs. • To assess and compare the blood sugar level changes of the patients at different time intervals. • Complications, if any were observed and noted on patients at different time intervals.